2021
DOI: 10.1590/1983-1447.2021.20200388
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in mothers of newborns in intensive care units

Abstract: Objective: To evaluate the classification and factors associated with anxiety and/or depression in mothers of newborns in a neonatal intensive care unit and elaborate the nursing process after psychological testing. Method: A study conducted with 91 mothers of newborns in intensive care of northeastern maternity, through a Beck anxiety and depression characterization and inventory form. Results: Majority with severe anxiety (93.4%) and moderate depression (50.5%). There was statistical significance between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Fathers typically experienced fewer depressive symptoms (ES, 0.12; 95% CI, 0.03–0.22; I 2 =85.6%; P <0.00) than mothers (ES, 0.31; 95% CI, 0.24–0.38; I 2 =91.5%; P <0.001) whose newborns were in the NICU [ 6 , 8 , 14 , 17 - 19 , 35 , 37 , 39 - 41 , 43 ]. An overall subgroup analysis revealed that 28% of parents were depressed about NICU admissions (ES, 0.28; 95% CI, 0.21–0.35; I 2 =94.6%; P <0.001) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fathers typically experienced fewer depressive symptoms (ES, 0.12; 95% CI, 0.03–0.22; I 2 =85.6%; P <0.00) than mothers (ES, 0.31; 95% CI, 0.24–0.38; I 2 =91.5%; P <0.001) whose newborns were in the NICU [ 6 , 8 , 14 , 17 - 19 , 35 , 37 , 39 - 41 , 43 ]. An overall subgroup analysis revealed that 28% of parents were depressed about NICU admissions (ES, 0.28; 95% CI, 0.21–0.35; I 2 =94.6%; P <0.001) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used the Hospital Anxiety and Depression Scale (ES, 0.45; 95% CI, 0.11–0.80; I 2 =98.6%; P <0.001) [ 28 - 30 , 44 ]. Two studies used Beck’s Anxiety Inventory scale (ES, 0.60; 95% CI, 0.04–1.25; I 2 =98.9%; P <0.001) [ 10 , 19 ]. Two studies used the Hamilton Anxiety Rating scale (ES, 0.42; 95% CI, 0.26-0.58; I 2 =90.7%; P <0.001 [ 14 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations